Impact and Lessons Learned from a National Consortium for Participatory Health Research: PartKommPlus—German Research Consortium for Healthy Communities (2015–2018). (17th September 2018) - Wright, Michael T.; Hartung, Susanne; Bach, Mario; Brandes, Sven; Gebhardt, Birte; Jordan, Susanne; Schaefer, Ina; Wihofszky, Petra
Abstract : Integrated strategies of health promotion at the municipal level are receiving particular attention in public health policy and practice in Germany. These strategies are intended to provide a coordinated approach to health promotion during the entire lifespan, with a particular focus on vulnerable communities. They are also intended to be participatory in both their design and implementation, involving all sectors of the social welfare, educational and healthcare systems, civil society, and the general public. PartKommPlus—German Research Consortium for Healthy Communities is examining such strategies using participatory forms of research. The goal is to determine how participation can best be planned and implemented and what effects this participation has. In this article the work of PartKommPlus from the first funding phase (2015–2018) will be described with particular attention to the lessons learned and the forms of impact which are being considered as part of the participatory research process.